Montmorillonite K-10 promoted synthesis of chiral dioxa-caged compounds derived from levoglucosenone - Zurita, Mariano (2015)
A short and efficient methodology for the synthesis of chiral dioxa-caged Compounds from levoglucose-none, a biomass-derived enone, is herein Presented. The key transformation, that involves a cascade 3-step cationic cyclization, was efficiently carried out in high yields and selectivities by Montmorillonite K-10 catalysis. The usefulness of K-10 in related semi-pinacol rearrangements to obtain pyran-3-ones is also shown. Interesting differences in the reactivity pattern was found for epimeric alcohols, and the origins of these findings were determined by DFT calculations.